Cecília Atienza: uma vida dedicada a biblioteconomia jurídica - NUNES, Alessandra Helena da Mata (2017)
Demonstrates and analyzes the contributions of the librarian, teacher and advocate Cecilia Andreotti Atienza Alonso on the stage of production of scientific and academic librarianship national legal. Presents itself, according on the nature of the data in qualitative character and develops through the inductive method, using the technique of indirect documentation and the extensive direct observation, the first through documentary research and bibliographic and the second by applying questionnaire, via email, to authority concerned. Prepares biography and bibliography of that librarian based on the main aspects of his professional career, academic and scientific. Presents the conceptual and documentary specimens of legal librarianship, as well as the most significant events that culminated in the emergence of this theme in Brazil. Performs brief remarks about the teaching of legal documentation in the country, demonstrating the historical and contemporary contributions of the discipline and the librarian Cecilia Atienza for this scenario. Shows the profile of the librarian who works in the legal field, its importance and challenges in the current panel. This is about the authors whose ideas formed the basis for studies of Cecilia Atienza in the area of information and legal documentation. Presents the authors influenced by the work of librarian and writing on the subject of librarianship in contemporary legal. Concludes that are crisp and very significant contributions to the librarian Cecilia Atienza area of legal librarianship from the 1970s until today, because today more than half of the papers on legal information and documentation mention at least one scientific productions of the authoress.